2017
DOI: 10.1038/s41598-017-03755-0
|View full text |Cite
|
Sign up to set email alerts
|

Trilocular phenotype in Brassica juncea L. resulted from interruption of CLAVATA1 gene homologue (BjMc1) transcription

Abstract: As a desirable agricultural trait, multilocular trait of rapeseed (Brassica rapa; Brassica napus; Brassica juncea), always represents higher yield per plant compared with bilocular plants. We previously isolated a trilocular gene locus, Bjmc1, and identified a set of molecular markers linked to the trilocular gene. With a map-based cloning, we identified that the BjMc1 was located in B genome of Brassica juncea, and it was a CLAVATA1 (CLV1) gene homologue. The insertion of a copia-LTR retrotransposable element… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(43 citation statements)
references
References 45 publications
0
42
1
Order By: Relevance
“…Thus, the double mutants of BnCLV3 generated in the present study might provide excellent starting materials for further high‐yield breeding in rapeseed. In B. juncea , a mutation in the CLV1 gene homologue on the B genome exhibited four valves stably in trilocular siliques (Xu et al ., ). Compared with the mutation phenotype of the same gene homologue in B. juncea , the phenotype of the double mutants of BnCLV1 generated in the present study was instable; that is, they produced a variable valve numbers in the siliques of the same plant and a lower percentage of multilocular siliques per plant (Table ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, the double mutants of BnCLV3 generated in the present study might provide excellent starting materials for further high‐yield breeding in rapeseed. In B. juncea , a mutation in the CLV1 gene homologue on the B genome exhibited four valves stably in trilocular siliques (Xu et al ., ). Compared with the mutation phenotype of the same gene homologue in B. juncea , the phenotype of the double mutants of BnCLV1 generated in the present study was instable; that is, they produced a variable valve numbers in the siliques of the same plant and a lower percentage of multilocular siliques per plant (Table ).…”
Section: Discussionmentioning
confidence: 97%
“…One and two recessive nuclear genes are responsible for the multilocular trait in B. rapa and B. juncea, respectively (He et al, 2003;Lv et al, 2012;Xiao et al, 2013). A single-nucleotide mutation in CLAVATA3 (CLV3) gene homologue and insertion of a copia-LTR retrotransposable element in CLAVATA1 (CLV1) gene homologue interrupt the function of the target genes and control the multilocular trait in B. rapa and B. juncea, respectively (Fan et al, 2014;Xu et al, 2017). In Arabidopsis, CLV3 acts as a small secreted peptide that interacts with a CLV1-CLV2-CORYNE (CRN)-RECEPTOR-LIKE PROTEIN KINASE2 (RPK2) receptor kinase-mediated pathway to repress the expression of the stem cell-promoting homeodomain transcription factor WUSCHEL in shoot apical meristems (SAMs) (Clark et al, 1993(Clark et al, , 1997Jeong et al, 1999;Kayes and Clark, 1998;Kinoshita et al, 2010;M€ uller et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The double and triple mutants of BAM1/2/3 genes displayed many defects in organ development, including reduced fertility and smaller leaf, flower and silique (DeYoung et al , ). Recently, the BjLn1 and BjMc1 gene (responsible for multilocular siliques) were successfully cloned, which was caused by the natural mutations in the CLV1 orthologues, respectively, on the A and B genome of Brassica juncea (Xiao et al , ; Xu et al , ). In recent years, the CLV ‐ WUS pathway has become an attractive target of genome editing for crop improvement (Rodriguez‐Leal et al , ), which has produced a series of exciting achievements.…”
Section: Receptor Kinase Signallingmentioning
confidence: 99%
“…Interestingly, many of these genes have a conserved function in regulating fruit development in both dry and fleshy fruit types, suggesting broad applicability of common genome edits. For instance, CYP78A9 and CLV‐WUS pathway genes can regulate both silique size in Arabidopsis /rapeseed (Fan et al , ; Shi et al , ; Xiao et al , ; Xu et al , ; Yang et al , ) and fruit size in cherry/tomato (Lemmon et al , ; Li et al , ; Qi et al , ; Rodriguez‐Leal et al ., ; Xu et al , ). Besides, many of these genes have similar functions in regulating fruit size in Arabidopsis and other crops.…”
Section: Conclusion and Future Prospectsmentioning
confidence: 99%
“…Xu et al . 13 reported that trilocular phenotype in B . juncea was caused by the insertion of a copia-LTR retrotransposable element in the coding region of BjMc1 .…”
Section: Introductionmentioning
confidence: 99%